MNIS+7 and lower limb function in inotersen treatment of hereditary transthyretin‐mediated amyloidosis. Issue 4 (13th August 2020) - Dyck, P. James B.; Kincaid, John C.; Wiesman, Janice F.; Polydefkis, Michael; Litchy, William J.; Mauermann, Michelle L.; Ackermann, Elizabeth J.; Guthrie, Spencer; Pollock, Michael; Jung, Shiangtung W.; Baker, Brenda F.; Dyck, Peter J.
Abstract: Introduction: Inotersen, an antisense oligonucleotide inhibitor of transthyretin (TTR) protein production, demonstrated significant benefit versus placebo in the modified Neuropathy Impairment Score (NIS) +7 neurophysiologic tests (mNIS+7) in patients with hereditary TTR‐mediated amyloidosis (hATTR) with polyneuropathy. This analysis assessed the mNIS+7 components by anatomic location and the lower limb function (LLF) test. Methods: Adults with hATTR in the NEURO‐TTR trial (NCT01737398) were randomly assigned to receive weekly doses of subcutaneous inotersen 300 mg or placebo for 65 weeks. The mNIS+7 and LLF were assessed at 35 and 66 weeks. Results: All major mNIS+7 components (muscle weakness, muscle stretch reflexes, sensation) and the LLF showed significant efficacy in patients receiving inotersen versus placebo; however, NIS‐reflexes (upper limb), touch pressure (upper and lower limbs), and heart rate during deep breathing did not show significant effects. Discussion: The results of this analysis reinforce the beneficial effect of inotersen on slowing neuropathy progression in patients with hATTR polyneuropathy. Abstract : See article on pages 509–515 in this issue .